2000
DOI: 10.1086/308618
|View full text |Cite
|
Sign up to set email alerts
|

TheHubble Space TelescopeSurvey of BL Lacertae Objects. I. Surface Brightness Profiles, Magnitudes, and Radii of Host Galaxies

Abstract: We report on a large HST imaging survey of BL Lac objects, at spatial resolution ∼ > 10 times better than previous ground-based surveys. We focus on data reduction and analysis, describing the procedures used to model the host galaxy surface brightness radial profiles. A total of 69 host galaxies were resolved out of 110 objects observed, including almost all sources at z ∼ < 0.5. We classify them morphologically by fitting with either an exponential disk or a de Vaucouleurs profile; when one fit is preferred … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
202
3
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(223 citation statements)
references
References 73 publications
17
202
3
1
Order By: Relevance
“…Any differences between our results and the P02 results should thus reflect differences in the analysis method. The third dataset comes from the HST study of Scarpa et al (2000a;hereafter SU00). All comparison sets have been analyzed with the same 1-dim analysis package, whereas we have used a 2-dim method.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any differences between our results and the P02 results should thus reflect differences in the analysis method. The third dataset comes from the HST study of Scarpa et al (2000a;hereafter SU00). All comparison sets have been analyzed with the same 1-dim analysis package, whereas we have used a 2-dim method.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
“…Abraham et al 1991;Stickel et al 1993;Wurtz et al 1996;Falomo & Kotilainen 1999;Scarpa et al 2000a;Urry et al 2000;Pursimo et al 2002) have shown that BL Lacs lie in the nuclei of luminous (M R ∼ −23.7) and large (r eff ∼ 10 kpc) elliptical galaxies. Their bulk properties appear to be indistinguishable from those of the host galaxies of Fanaroff-Riley (FR) type I radio sources (Fanaroff & Riley 1974), supporting the unifying view that BL Lacs are FR I radio sources seen almost along the direction of the jet (Urry & Padovani 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We have also reported the core dominance (CD) parameter in the R band, i.e. the ratio between the nuclear intensity to that of the host galaxy, collected from the literature (Wurtz et al 1996;Scarpa et al 2000). It is apparent that the WDP is different for the various sources.…”
Section: Discussionmentioning
confidence: 99%
“…For objects observed in more than one night, the weighted average is given. c Ratio between nuclear and galactic flux in R band (Wurtz et al 1996;Scarpa et al 2000). d Magnetic field intensity in Gauss (Ghisellini et al 1998;Tagliaferri et al 2001).…”
Section: C 66amentioning
confidence: 99%
“…Using the A λ versus λ relationship of Cardelli et al (1989) we found the extinction (in magnitudes) in the B, R, and I filters: A B = 0.53, A R = 0.30, and A I = 0.19. Finally, we converted the dereddened magnitudes into flux, without applying any correction for the contribution of the host galaxy, as it cannot be resolved even in deep HST images (Scarpa et al 2000). be observed in most of the S4 0954+658 light curves.…”
Section: Observations and Data Reductionmentioning
confidence: 99%